2018
DOI: 10.1103/physrevd.98.063529
|View full text |Cite
|
Sign up to set email alerts
|

Impact of EDGES 21-cm global signal on the primordial power spectrum

Abstract: We investigate the impact of the recent observation of the 21cm global signal by EDGES on primordial power spectrum, particularly focusing on the running parameters α s and β s which characterize the detailed scale dependence of the primordial spectrum. When primordial power spectrum is enhanced/suppressed on small scales, the structure formation proceeds faster/slower and changes the abundance of small size halos, which affects the sources of Lyman α radiation at high redshifts to alter the position of the ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 115 publications
0
18
0
Order By: Relevance
“…Here, as in Refs. [22][23][24][25][26][27]39], we take advantage of this lower bound on the amount of Lyman-α photons to probe different dark-matter models. We will phrase the EDGES requirement in terms of the dimensionless coupling coefficient x α , which enters in the definition of the spin temperature (ignoring collisional coupling during cosmic dawn) as…”
Section: E Edges Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Here, as in Refs. [22][23][24][25][26][27]39], we take advantage of this lower bound on the amount of Lyman-α photons to probe different dark-matter models. We will phrase the EDGES requirement in terms of the dimensionless coupling coefficient x α , which enters in the definition of the spin temperature (ignoring collisional coupling during cosmic dawn) as…”
Section: E Edges Datamentioning
confidence: 99%
“…Previous works have studied the effect of non-CDM models on the 21-cm signal [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Those models typically suppress the matter power spectrum beyond some wavenumber k, delaying the onset of cosmic dawn.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the EDGES result is difficult to explain by the standard scenario: The amplitude of the absorption trough is almost twice as large as the maximal value expected in the standard cosmology. However, instead of giving an explanation on this anomaly, several authors have already applied the EDGES result to constrain some models: the Hawking evaporation of small primordial black holes (PBHs) (Clark et al 2018), the emission from the accretion discs around large PBHs (Hektor et al 2018), the decaying (Clark et al 2018;Mitridate & Podo 2018) or annihilating dark matter (Cheng et al 2018;D'Amico et al 2018), warm dark matter (Safarzadeh et al 2018), primordial power spectrum (Yoshiura et al 2018) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Since the amplitude of primordial fluctuations changes how structure formation proceeds, which affects the timing when Lyman α photon sources are switched on, then in turn, changes the structure of the global signal of neutral hydrogen 21cm line. Indeed, in our previous work [9], we have derived constraints on the so-called running parameters, which are commonly used to characterize higher order scale-dependence of primordial power spectrum and denoted as α s and β s , using this argument in the light of recent report from the EDGES low band result [10] where the absorption trough is detected at the frequency of ν = 78 MHz, corresponding to the redshift of z ∼ 17.2 #1 . In [9], we have shown that, by just using the information of the position (frequency) of the absorption trough, one can derive the constraint on α s and β s whose uncertainties are comparable to Planck #2 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in our previous work [9], we have derived constraints on the so-called running parameters, which are commonly used to characterize higher order scale-dependence of primordial power spectrum and denoted as α s and β s , using this argument in the light of recent report from the EDGES low band result [10] where the absorption trough is detected at the frequency of ν = 78 MHz, corresponding to the redshift of z ∼ 17.2 #1 . In [9], we have shown that, by just using the information of the position (frequency) of the absorption trough, one can derive the constraint on α s and β s whose uncertainties are comparable to Planck #2 . Here it should be noted that, although it is very common to parametrize primordial power spectrum with the spectral index n s and its runnings α s , β s , these parameters are usually defined at a reference wave number on large scale, which means that we extrapolate the power spectrum to smaller scales.…”
Section: Introductionmentioning
confidence: 99%